Ten Years of Landscape Genomics: Challenges and Opportunities - Li, Yong; Zhang, Xue-Xia; Mao, Run-Li; Yang, Jie; Miao, Cai-Yun; Li, Zhuo; Qiu, Ying-Xiong (Frontiers in Plant Science, 2017)
Landscape genomics is a relatively new discipline that aims to reveal the relationship between adaptive genetic imprints in genomes and environmental heterogeneity among natural populations. Although the interest in landscape genomics has increased since this term was coined, studies on this topic remain scarce. Landscape genomics has become a powerful method to scan and determine the genes responsible for the complex adaptive evolution of species at at population (mostly) and individual (more rarely) level. This review outlines the sampling strategies, molecular marker types and research categories in 37 articles published during the first 10 years of this field (i.e., 2007–2016). We also address major challenges and future directions for landscape genomics. This review aims to promote interest in conducting additional studies in landscape genomics.